Comparative analysis of pejerrey fish (Odontesthes bonariensis) gonadal development during two consecutive spawning seasons in relation to sex steroids and temperature variation in cochicó lake (Pampas region, Argentina) - del Fresno, Pamela Sabrina (2021)
Cochicó belongs to “Encadenadas del Oeste” system of lakes being a typical water body of the Pampas region. The most abundant fish species in this lake is the pejerrey (Odontesthes bonariensis) valued due to the quality of its flesh and as a game fish. The aim of this study was to compare the gonadal stages of pejerrey during two consecutive spawning seasons (August to December) in relation to sexual steroids and temperature in this lake. In general, pejerrey gonadal development, the Gonadosomatic index and the plasma levels of estradiol and testosterone fluctuated in relation with temperature. In 2014 samplings, females started to ovulating in early August, with a peak during September-October and ending in December with many of them with atretic oocytes. However, in 2015, a marked delay in maturation was observed with ovulated fish only in October and December. This fact may be because the minors mean temperatures recorded in this year. For males, it was possible to find spermiating animals during the whole spawning season and only arrested animals in December. Unexpectedly, histological gonadal analysis revealed for the first time pejerrey with testis-ova, probably due to the intensive use of agrochemicals in this region.